Characterization of 50 nm MOSFET with dielectric pocket - Fauzan, Zul Atfyi; Saad, Ismail; Ismail, Razali (Malaysian Institute of Physics, 2007)

(untitled)
Characterizat ion of a metal-oxide-semi conductor field effect tran sistor incorporating dielectric pocket (DP) for suppression of short-channel effect (SCE ) is demonstrated by using 2D numerical simulation. An analysis of 120 nm and 50 nm channel length (LJ wit h DP incorp orated between the chann el and source/drain has been done successfu lly. The DP has suppressed short channel effect (SCE) witho ut the need s of increasi ng the channel dopin g pro file. With uniform dopi ng of 10" em' and 10' 0 ern' for channel and source/drain region respectively, a reduc tion of 2.5 decade s of leakage current (lOFF) was obtained in MOSFET with DP without altering the drive current (ION) for 120 nm channe l length . A very low leakage current of 0.002 pAl l'm is obtained for DP device with drain voltag e (Vos) of 0.1 V and increase to 18 pAll'm with Vns = l.OV for 120 nm Lg. Th is obtained with drive current of 0.5 rnA and 5 rnA respectively. Meanwhile, with L. = 50 nm, 700 nAll'm leakage current and 1 mAll'm drive current was o bserved. With the same doping profile s, a reduct ion of 1.4 decades of 10 FF was shown by the incorpora tion of DP for Lg = 50 nm. Thus, the incorporation of DP will enhance the electri cal perform ance and give a very good control of the SCE for sca ling the MOSFET in nanometer regime for future developme nt of nanoe lectronics product.